Implementasi Strategi Digital Marketing Melalui Sosial Media Intagram Dalam Meningkatkan Minat Berkunjung Followers Terhadap Kedai Kopi Difisi Coffee - Jamil, Farhan; Wulansari, Nuni; Irawansah, Opi (Peneliti.net, 2025)
Instagram has become one of the most popular social media platforms for product promotion activities. The purpose of this study was to assess the influence of Instagram Difisi Coffee on visitor interest. The study was conducted using a correlation test technique to determine the relationship between variables (X) and variables (Y). The research that has been conducted obtained results stating that there are positive and negative influences from the Instagram content @difisicoffee on visitor interest.